The drought of 1887, and some of its effects on Irish agriculture: maps - Barrington, Richard M. (Statistical and Social Inquiry Society of Ireland, 1888)
Maps showing distribution of rainfall in Ireland
Maps: [Drought of 1887, and some of its effects on Irish agriculture]
Keywords: Maps; Drought; 314.15